2022
DOI: 10.3390/ijerph19137576
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in Relation to Metabolic Disorders and the Concentration of Sex Hormones in Aging Men

Abstract: Background: The aim of this study was to analyze the relationship between the prevalence of erectile dysfunction in men as diagnosed by the International Index of Erectile Function (IIEF) questionnaire and the respective levels of sex hormones and biochemical parameters, as well as indices of visceral fat accumulation and activity. Material and Methods: The study comprised 148 male (60–75 years) patients from primary care outpatient clinics in the city of Szczecin (Poland). The men were asked to complete a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Because the VAI formulates both structural and functional elements meaning that VAI contains both physical and metabolic parameters, so, VAI could be valuable index of both fat distribution and function. In agreement with our research, other reports of Akdemir et al (8), Aleksandra et al (12) showed that evaluation utilising indices like VAI, which showed that excessive visceral fat accumulation increases risk of developing ED, appears to be more reliable than using anthropometric parameters like BMI or WC. Consistent with our findings and that of the others, it has been demonstrated that VAI was independently related to cardiovascular events (8,13) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because the VAI formulates both structural and functional elements meaning that VAI contains both physical and metabolic parameters, so, VAI could be valuable index of both fat distribution and function. In agreement with our research, other reports of Akdemir et al (8), Aleksandra et al (12) showed that evaluation utilising indices like VAI, which showed that excessive visceral fat accumulation increases risk of developing ED, appears to be more reliable than using anthropometric parameters like BMI or WC. Consistent with our findings and that of the others, it has been demonstrated that VAI was independently related to cardiovascular events (8,13) .…”
Section: Discussionsupporting
confidence: 93%
“…Several research have examined utility of VAI to distinguish existence of ED in hyperlipidemia, have set cut-off points, and have advocated it as best predictor of ED given necessity for early detection and treatment of ED to limit its morbidity (8,11,12) . Several studies have demonstrated a connection among ED and measurements of fat accumulation such VAI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of moderate-to-severe ED was 63% within our population, rising to 84% in patients experiencing at least mild ED. The recorded prevalence of at least mild ED ranges from 63 to 68% in studies that employ the same screening questionnaire for ED in primary care settings [ 69 ] and in community-based research [ 70 ]. However, in primary care, symptoms of ED are often not fully disclosed due to various factors such as reporting bias, cultural influences, physicians’ failure to inquire about patients’ sexual health, and the social stigma surrounding the condition [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…En ese sentido, la valoración inicial de los pacientes con de en su consulta de atención primaria debe incluir la búsqueda de factores de riesgo clínicos como la presencia de obesidad, ya que se trata de un factor modificable que influye en el desempeño sexual. 25,26 En cuanto al tratamiento, 30% de los hombres que usan medicamentos para de reportaron mal uso. 16 Un estudio realizado en Costa Rica, detectó que 35% de quienes consumen sildenafil son hombres entre 25 y 35 años.…”
Section: Discussionunclassified